Teachers' Perspective on Strategy for Teaching English Vocabulary to Young Learners - Deni, Rahma; Fahriany, Fahriany (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2020)
Teaching and learning vocabulary is an integral part of foreign language learning since it is the basic sub-skill for someone who wants to learn a foreign language. Thus, it is essential to teach English vocabulary at an early age since students still in the scope of their golden age, and they could learn everything easily. In this case, the teachers' teaching strategy seems essential to be concerned. Moreover, this descriptive qualitative study as a case study is designed to explore the Qur'an Learning Center teachers' perspective on the strategy used to teach vocabulary to young learners. The data were gathered through a semi-structured interview with two English Teachers at the Qur'an Learning Center, one of the elementary schools in Jakarta Selatan. The result of this study revealed that teachers believe that teaching strategy is essential for teaching vocabulary to young learners. Thus, the teachers have various strategies that can be applied for teaching vocabulary to young learners, for example, using games, sing a song, and others. Also, the teachers used interesting media like video, a real thing, pictures, and others. Those strategies are effective in engaging students to learn new vocabulary in English. This study is expected to give reference and knowledge for the English teacher who teaches young learners so they could implement some suitable ways with their real class.